NEW APPROACHES TO CONDUCTING AGROCHEMICAL RESEARCH UNDER CONDITIONS OF GLOBAL CLIMATE CHANGE - Kuziev J. M. (Web of Journals Publishing, 2025)
The article provides information about the reasons for changes in the agrochemical properties of irrigated soils in the republic. As part of scientific projects, agricultural technologies have been created to develop the ratio of NPK mineral fertilizers for cotton under conditions of global climate change. It has been established that in these conditions for the cultivation of agricultural plants, the ratios of mineral fertilizers used do not satisfy their needs, which necessitates the need for in-depth scientific research to solve this problem.
Keywords: Soils, fertility, agrochemical research, ratios, NPK, mineral fertilizers, innovation, agricultural technologies, climate change.